Cartographers : Zagreb - Warszaw - Budapest - Maribor : Geo-Gnostic Projection for the 21st Century. - Beke, László; Blom, Ina; Curnow, Wystan; Günther, Ingo; Koscevic, Zelimir; Krukowski, Wojcijech; Lapaine, Miljenko; Millet, Catherine; Prosenc, Meta Gabrsek; Rogoff, Irit; Safred, Laura; Storr, Robert; et al. (Zagreb : Muzej Suvremene Umjetnosti, 1997)
Baldyga, Janusz ; Ben ; Bijelic, Milivoj ; Boezem, Marinus ; Brown, Robert Delford ; Bukta, Imre ; Cattelan, Maurizio ; Chubb, Shirley ; Chunn, Nancy ; Dan, Calin ; Delvoye, Wim ; Dimitrijevic, Braco ; Dluzniewski, Andrzej ; Droese, Felix ; Druks, Michael ; Durham, Jimmie ; Earth, Ocean ; Erdogmus, Tayflin ; Fairchild, Anna ; Fischer, Daniel ; Galantai, Gyorgy ; Garbin, Aleksandar ; Günther, Ingo ; Hadzifejzovic, Jusuf ; Higgins, Dick ; Huerta, Benito ; IRWIN ; Jovanovski, Zarko ; Jukic, Sanjin ; Jung, Krzystof ; Katchadourian, Nina ; Kentridge, William ; Kivi, Jussi ; Kuduz, Ante ; Kuitca, Guillermo ; Ladovic, Renata ; Lalibert, Otis ; Langa, Moshekwa ; Limite, Equipo ; Lukac, Jenni ; Mangelos ; Martek, Vlado ; Meel, Raoul ; Mulkers, Urbain ; Nordo, Guttorm ; Ohrt, Roberto ; Onlir, Füslin ; Ono, Yoko ; Ozbolt, Alen ; Paik, Nam June ; Patterson, Simon ; Peljhan, Marko ; Pogacar, Tadej ; Ramos, Ibrahim Mirando ; Rihs, Christoph ; Romanos, Chryssa ; Schmit, Tomas ; Schuster, Michael ; Sikora, Rudolf ; Sikorski, Tomasz ; Siliik/Klirpershoek ; Solomko, Juri ; Vitone, Luca ; Watson, Ruth ; Willmann, Manfred ; Wilzig, Annette ; Wrobel-Klilik, Brygida ; Ziljak, Vilko
biografie
Cartographers : Geo-Gnostic Projection for the 21st Century, Muzej Suvremene Umjetnosti, Zagreb, 8.6. - 27.7.1997 ; Center for Contemporary Art, Zamek Ujazdowski, Warzaw, January 16 - February 22 1998 ; Mücsarnok, Budapest, April - May 1998 ; Umetnostna Galerija, Maribor, May 12 - June 20 1998
Kroatisch & Engels
kunstcatalogus